Kematian Fisik Dan Pentingnya Persiapan Rohani Menurut Alkitab - Yasrin Mesalayuk; Aprianus Lendik Boimau (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This research uses qualitative methods;By conducting a literature review from various sources such as books, articles, and other references. This article presents the idea of physical death and the importance of biblical spiritual preparation to help believers not mistakenly respond to human death. Given some people's mistaken view of death and where people's spirits go after death, this study will give the idea that death in the Christian faith is the reward of human sin but that God is blessed with His loved ones. The results of the analysis show that a straightforward view of the judgment of death, and where people go after death, must be viewed based on what the Bible itself says, so that we do not follow certain cultural currents that still emphasize the presence of spirits of the dead in their lives.